FRI0065 Residual power doppler signals during clinical remission determine joint prognosis in rheumatoid arthritis. (23rd January 2014) - Yoshimi, R.; Takase, K.; Hama, M.; Kishimoto, D.; Terauchi, K.; Watanabe, R.; Uehara, T.; Samukawa, S.; Ihata, A.; Ueda, A.; Takeno, M.; Ishigatsubo, Y.
Abstract : Background: "Clinical remission" has been a realistic goal of treatment in rheumatoid arthritis (RA). However, there is evidence that subclinical synovitis is associated with progression of structural damage even after achieving clinical remission, 12 which could reflect the inadequate sensitivity of the conventional clinical approaches to detect synovitis. Objectives: Here we prospectively assessed RA patients in clinical remission to clarify whether ultrasonography (US) can predict long-term radiographic progression during persistent clinical remission. Methods: Twenty-seven RA patients in clinical remission (DAS28-ESR <2.6 or DAS28-CRP <2.3) were recruited. Bilateral wrists, and all of MCPs and PIPs were examined by power Doppler (PD) US. Gray scale (GS) and PD signals were scored in each joint from 0 to 3, respectively. Total PD score and total GS score were calculated by summing up the score of individual joints. Hand X-ray was performed at entry and at 2 years. Patients were defined as radiographically progressing cases when the change of the van der Heijde-modified total Sharp score exceeded 0.5 units per year and the others were as non-progressing cases. In principle, therapy was not modified during the study, unless the patients had clinical flare-up. Results: Twenty-two patients maintained clinical remission during the 2-year follow-up, while 5 had clinical flare-up. The persistent remission group was further divided into 7 progressing cases (32%) and 15 non-progressing cases (68%) based on X-ray findings. There was no significant difference in age (51.4±7.74 vs 59.2±12.1 years, p =0.15) and disease duration (7.3±3.9 vs 6.7±3.7 years, p =0.74) at entry between the two groups. Progressive radiographic destruction was strongly associated with total PD score at entry, but not with total GS score. Progressive radiographic destruction in any joints was found in 7 of 11 patients (64%) having more than 2 of total PD score at entry, but none of the other 11 having PD score 0 or 1. There was no significant association of therapeutic agents with radiographic progressing. When the persistent clinical remission group was further divided into 12 TNF inhibitor (TNFi)-free and 10 TNFi-treated cases, total PD score was significantly higher in patients with radiographic progression than in those without progression in both the TNFi-free (2.75±0.83 vs 0.63±0.86, p =0.0039) and TNFi-treated groups (10.3±7.93 vs 1.14±1.36, p =0.029). However, no significant difference was found in radiographic progression between the TNFi-free and TNFi-treated groups when these are compared in the same total PD score categories. Conclusions: PDUS detects latent synovitis causing joint destruction even in the clinical remission of RA patients, irrespective of TNFi therapy. Thus, US is a potent tool for prediction of joint prognosis during clinical remission of RA. References: Mulherin D, Fitzgerald O, Bresnihan B. Clinical improvement and radiological deterioration in rheumatoid arthritis: evidence that the pathogenesis of synovial inflammation and articular erosion may differ. Br J Rheumatol 1996;35:1263-8. Molenaar ET, Voskuyl AE, Dinant HJ, et al. Progression of radiologic damage in patients with rheumatoid arthritis in clinical remission. Arthritis Rheum 2004;50:36-42. Disclosure of Interest: None Declared